Smallholder agriculture and climate change adaptation in Bangladesh: questioning the technological optimism. (7th June 2017) - Misra, Manoj
Abstract : This paper offers an in-depth sociological analysis of how the interplay of climatic factors, agricultural technologies and markets shapes smallholder livelihoods in Bangladesh to help sketch the outline for a sustainable agricultural adaptation strategy. It intends to question the technological optimism inherent in mainstream climate change policy discourse by highlighting the multiple sources of vulnerabilities of smallholder peasants in Bangladesh. Using findings from a qualitative study, it demonstrates how smallholders in Bangladesh currently experience climate change through their everyday agricultural practices, and how climate change along with the ecosystem destruction from modern farming technologies adversely affects their livelihoods. Drawing on the recent literature on sustainable adaptation, this paper argues that any agricultural adaptation strategy in Bangladesh must analyse the vulnerabilities of farming communities at the intersection of their geographically specific exposure to climatic threats, the extent of their market participation and the socioecological implications of their technology adoption. It concludes that an eventual departure from the current rice monoculture pivoted on chemical dependence and an excessive use of natural resources is the prerequisite for a sustainable agricultural adaptation.